Malaspina 2010: observaciones de R/ETS - Maldonado Uribe, Federico (2012)
Respiratory electron transport system (ETS) activities have been used, in the past, to study respiration in many marine organisms and many different environments. The methodology follows standard practices of enzymology, by attempting to measure the maximum velocity of the enzyme reaction (Vmax) sensu Michaelis-Menten. Under controlled conditions of nutritional state the ETS method is well correlated with in situ respiration. In the interdisciplinary Expedition MALASPINA 2010, that circumnavigated the planet, we had the chance in three of seven transects (Cape Town to Perth; Perth to Sydney and Cartagena de Indias to Cartagena) to take zooplankton samples from the southern Indian Ocean and from North Atlantic Ocean. From these samples we measured protein and 150 ratios between in vivo respiration and potential respiration (ETS activity) in three size-classes of zooplankton between 100?m to > 1000?m, in the upper 150 meters of the water column. Normally, the measurements were made on fresh naturally nourished zooplankton (in situ). When biomass permitted, measurements were also made on zooplankton starved for 24 h. With this data we are investigating the variations in the R/ETS ratio and Kleiber?s law under different nutritional conditions, different oceanographic conditions, and different oceanographic regions. This analysis will help our ongoing investigation of ETS activity as an index of both respiration and of living biomass. The information acquired will facilitate the calculation of zooplankton respiration for some relatively unexplored areas of the Indian and Atlantic oceans. This data will then be available for integration with results of other Malaspina research programs